3D pointcloud data of the world's tallest tropical tree to date - Shenkin, A; Wilkes, P; Burt, A; Jami, U; Disney, M; Bentley, L; Malhi, Y (University of Oxford, 2019)
This data was generated from fusing 2 data sources: 1) pointclouds derived from co-registered terrestrial laser scans (TLS) using a Riegl VZ-400 (RIEGL Laser Measurement Systems GmbH); and 2) pointclouds derived from applying structure-from-motion algorithms to video from a UAV flight up and around the tree. Still images were extracted from the UAV-based video footage using ffmpeg, and these were then used to create pointclouds using Pix4Dmapper software package (Pix4D SA,. Switzerland). The TLS and UAV-dervied pointclouds were fused together using CloudCompare software (version 2.10.1, retrieved from http://www.cloudcompare.org/), and the TLS points were colored based on the color of the nearest neighboring UAV point. File contents are as follows: 1) Danum_tall_tree_Menara_-_TLS_data.txt = TLS pointcloud data of Menara. 2) Danum_tall_tree_Menara_-_fused_TLS_UAV_data.txt = fused TLS + UAV pointcloud data. 3) Area_surrounding_Menara_-_fused_TLS_UAV_data.laz = fused TLS + UAV pointcloud data of area surrounding Menara. 4) Menara_QSM.mat = Matlab file of TreeQSM structural model of Menara. 5) menara_cyls.csv = structural model of Menara in cylinder format. 6) Menara_pointcloud_orbit.avi = rendered video orbiting Menara. 7) Menara_TLS_UAV_fused_vertical_climb.avi = rendered video climbing from base to top of Menara. 8) Menara_TLS_rotation.avi = rendered video of TLS pointcloud. 9) Menara_TLS_UAV_fused_rotation.avi = rendered video of fused TLS + UAV pointcloud. For further information, please see Item_description_documentation.docx deposited with the data. This data results from the recent discovery of the world’s tallest tropical tree (Shorea faguetiana), possibly the world’s tallest angiosperm, located in the rainforests of Sabah, Malaysian Borneo. Through consideration of both mechanical (risk of wind damage) and ecophysiological constraints we argue in publications related to this data that this tree is close to the maximum height possible for angiosperms (flowering plants), around 100 m.